Private Voting in Electoral Legislation - Al-Barzanji, Sarhang Hamid; Shaker, Dalia Shirko (Journal of Legal and Political Studies, 2016)
"In this era we need to know that elections don't only include civilians participating day, but there are also some aspects that might not be noticeable , Especially in case of voting of soldiers, patient, disabled, people or civilian living abroad. This research aims to determine these important subjects according to law and constitution and ways to describe it to obtain results for improving election in Kurdistan. The approach taken in this study is the analytical and comparative method of electoral legislations under different electoral systems include Iraq and the Arab countries, and the electoral legislations in both of the united Kingdom, Australia, Sweden, India on the subject of special or early voting. We have addressed the subject of study in three sections, in the first section we dedicated the define of the special voting and the aim behind it, while the second part, we have considered the groups covered by the special vote, while we have dedicated the third and the last section of the study to the position of electoral legislations of this type of vote."
Keywords: Elections; Constitution; Voting; electoral legislations